(untitled) (Revista Internacional de Ingeniería de Estructuras, 2023)
Limited Ductility Wall Buildings (EDML, in Spanish) are predominantly used as social housing in Peru. Due to some of their characteristics, their seismic performance is estimated to be lower than that of buildings with conventional reinforced concrete walls. Different protection technologies can be used to improve their performance during strong earthquakes, but these may be economically unfeasible. For this reason, this research evaluates the feasibility of implementing a seismic isolation system in an EDML located in Peru’s highest seismic hazard zone, a property not yet built and representative of those existing on the Peruvian coast. The objective is to quantify the over-cost of seismically isolating an EDML in a risk context. Two types of buildings have been proposed to carry out this task: one with a fixed base and another with the same layout and type of walls but implemented with seismic isolators at its base. Both buildings were modelled computationally to analyze and design them structurally. Based on the blueprints resulting from the structural design, the construction costs of the two buildings were estimated and compared. The results show that the seismic isolation of the chosen EDML effectively reduces its seismic design loads. However, the cost reduction in the superstructure is not enough to offset the cost of implementing the isolation system. Finally, it is concluded that isolating the chosen EMDL with the proposed seismic isolation system is not economically attractive.